Moving an exercise referral scheme to remote delivery during the Covid-19 pandemic: an observational study examining the impact on uptake, adherence, and costs - Newby, Katie; Howlett, Neil; Wagner, Adam P.; Smeeton, Nigel; Fakoya, Olujoke; Lloyd, Nigel; Freethy, Imogen; Bontoft, Charis; Brown, Katherine; McKibben, Mary-Ann; Petherick, Annie; Wills, Wendy (BMC public health, 2024)
Background Exercise Referral Schemes (ERSs) have been implemented across Western nations to stimulate an increase in adult physical activity but evidence of their effectiveness and cost-effectiveness is equivocal. Poor ERS uptake and adherence can have a negative impact on effectiveness and cost-effectiveness and, if patterned by socio-demographic factors, can also introduce or widen health inequalities. Different modes of ERS delivery have the potential to reduce costs and enhance uptake and adherence. The primary aim of this study was to examine the effect of different programmes of ERS delivery on scheme uptake and adherence. Secondary aims were to examine the effect of socio-demographic factors on scheme uptake and adherence, and the impact of delivery mode on the expected resource and corresponding costs of delivering core parts of the programme. Methods This was an observational cohort study with cost analysis. Routine monitoring data covering a three-year period (2019–2021) from one large UK ERS (number of patients = 28,917) were analysed. During this period three different programmes of delivery were operated in succession: standard (all sessions delivered face-to-face at a designated physical location), hybrid (sessions initially delivered face-to-face and then switched to remote delivery in response to the Covid-19 pandemic), and modified (sessions delivered face-to-face, remotely, or a combination of the two, as determined on a case-by-case basis according to Covid-19 risk and personal preferences). Multi-level binary logistic and linear regression were performed to examine the effect of programme of delivery and socio-demographic characteristics on uptake and adherence. Cost data were sourced from regional-level coordinators and through NERS audits supplied by national-level NERS managers and summarised using descriptive statistics. Results There was no effect of programme of delivery on scheme uptake. In comparison to those on the standard programme (who attended a mean of 23.1 exercise sessions) those on the modified programme had higher adherence (mean attendance of 25.7 sessions) while those on the hybrid programme had lower adherence (mean attendance of 19.4 sessions). Being older, or coming from an area of lower deprivation, increased the likelihood of uptake and adherence. Being female increased the chance of uptake but was associated with lower adherence. Patients referred to the programme from secondary care were more likely to take up the programme than those referred from primary care for prevention purposes, however their attendance at exercise sessions was lower. The estimated cost per person for face-to-face delivery of a typical 16-week cycle of the scheme was £65.42. The same cycle of the scheme delivered virtually (outside of a pandemic context) was estimated to cost £201.71 per person. Conclusions This study contributes new evidence concerning the effect of programme of delivery on ERS uptake and adherence and strengthens existing evidence concerning the effect of socio-economic factors. The findings direct the attention of ERS providers towards specific patient sub-groups who, if inequalities are to be addressed, require additional intervention to support uptake and adherence. At a time when providers may be considering alternative programmes of delivery, these findings challenge expectations that implementing virtual delivery will necessarily lead to cost savings.